Evaluación de la calidad físico-química de la carne fresca bovina procedente de sitios de abasto de la zona céntrica de la ciudad de Babahoyo - Angulo Ortiz, Iris Alejandra (2024)
The present study focused on evaluating the physicochemical quality of fresh beef from 23 supply sites located in the central area of the city of Babahoyo, Ecuador. Critical variables such as temperature, pH, moisture, and cooking loss were analyzed in a total of 46 meat samples. The results obtained revealed significant deviations from the ideal standards described in the scientific literature. The average recorded temperature (24.28°C ± 2.26°C) considerably exceeded the recommended range of 0-4°C, the average pH (6.40 ± 0.21) was higher than the optimal range of 5.4-5.8, the average moisture (51.26% ± 20.88%) was lower than the ideal of 70-75%, and the average cooking loss (26.26% ± 29.96%) exceeded the desirable value of less than 20%. Statistical analyses, including ANOVA and correlation tests, showed significant differences among the supply sites for the variables of pH and cooking loss. Furthermore, important correlations were found between the studied variables, highlighting the strong inverse relationship between temperature and moisture (r=-0.90). These findings indicate that the quality of the meat in these establishments is not optimal, and substantial improvements are required in aspects such as refrigeration, moisture control, maturation processes, and staff training to ensure product safety and quality.